Sullivan, Phyllis. 1. Part one of interview about Pouch Cove. - Chun Lau, Po
Phyllis Sullivan is seated on her couch at her home in Pouch Cove, talking about picking berries. 00:00 – filling boxes with blueberries and selling them; picking in mountains past Shoe Cove; 0:46 – partridge berries, raspberries for jam; rhubarb jam.